356 Intraoperative Robotic Planning Software is Accurate at Predicting Postoperative Lumbar Lordosis After Anterior Column Reconstruction. (April 2023) - Shah, Vaibhavi; Haider, Ghani; Stienen, Martin N.; Veeravagu, Anand
Abstract : INTRODUCTION: Re-establishment of lumbar lordosis with spine deformity surgery is considered a pre-requisite for long term positive results with less biomechanical loading on the adjacent segments, reducing the likelihood of developing adjacent segment disease. The pre-operative planning softwares of robotic systems now allow the surgeon to plan a patient-specific surgical plan and are also able to predict the degree of lumbar lordosis following the instrumentation surgery based on pre-operative imaging by using vertebral segmentation. METHODS: We conducted a retrospective review of patients aged 18 or older who underwent pedicle screw spinal instrumentation using the Mazor X Robot (Medtronic Inc., Minneapolis, MN, USA), performed by one surgeon over a five-year period. The robotic guidance software (Mazor X-Align, Medtronic Inc., Minneapolis, MN, USA) was used to calculate the predicted lumbar lordosis based on pre-operative imaging. Wilcoxon Rank test was used to compare the predicted angles to the observed lumbar lordosis on post-operative radiographs. RESULTS: A total of 15 patients (46.6% female) with a mean age of 61.5 ± 10.9 years were identified, who underwent posterior lumbo-sacral spinal fusion with the robotic system using both percutaneous and open approach. Instrumentation was done across a mean of 3.27 levels per case and 11 patients (73.3%) underwent anterior column reconstruction prior to posterior fixation without the need for an intra-operative CT spin. There was no statistical difference between the predicted and the actual post-operative lumbar lordosis (p-value: 0.334) while there was a significant statistical difference between the pre-operative and post-operative angles (p-value: 0.02). CONCLUSIONS: Our study suggests that the intraoperative robotic planning software of the Mazor X system is accurate at predicting postoperative lumbar lordosis which can be useful and help guide surgical decision making and planning.